Evaluasi Kerapatan Jaringan Stasiun Hujan Di DAS Kali Pepe - Taufik, Rokhyat, Jaji Abdurrosyid, ST., MT (2016)
Kali Pepe river flows from Merbabu Mountain to Bengawan Solo river with total watershed area of 300,449 km2. The river passes the regions of Boyolali and Solo, and it is very important for the drainage of the Solo city. That is why many rainfall stations were installed alongside Kali Pepe river.The rainfall stations are to obtain the intensity and depth or rainfall in the area so the amount of rain water that will flow to Kali Pepe river will also be known. The density evaluation of rainfall stations of Kali Pepe watershed is conducted by using methods of Kagan, Narayanan, and Stephenson. The data available are daily rainfall and monthly rainfall. Those data then being analyzed using Kagan, Narayanan-Stephenson and Sri Harto-Vermeulen menthods to obtain the density of rainfall stations. Based on analytical result by methods of Kagan, Narayanan-Stephenson and Sri Harto-Vermeulen, by Kagan method it is obtaned that the number of rainfall stations is less than the number required, so it is necessary to provide more rainfall stations for further analysis. For daily rainfall with 5% error, it needa 0,224 km2/station hence 1336 rainfall stations are required. For 10% error, the density is 0,894 km2/station hence 336 rainfall stations are required. By Narayanan-Stephenson method it is obtamed that the number of rainfall stations required are 134. And by Sri Harto- Vermeulen method, for 5% error it requres 260 rainfall stations and for 10% error it requires 72 rainfall stations.